2017
DOI: 10.1262/jrd.2016-107
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of calcium channels and intracellular calcium in bull sperm thermotaxis

Abstract: Thermotaxis that sperm migrate to higher temperature area has been confirmed in rabbit and human. In this study, we examined the migration ability of bull sperm in a temperature gradient to confirm thermotaxis and elucidate the involvement of calcium in such thermotaxis, as well as the relation between sperm capacitation and bull fertility. Thermotaxis was evaluated in a temperature gradient of 34–42ºC using a cross-type column 22-mm long, 40-mm wide, and 100-μm deep. Significantly more sperm migrated to the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Another physical environment that worked on to facilitate sperm migration to the upper layer of the conical vessel is thermotaxis It has been reported that the migration of sperm in the female reproductive tract associated with fertilization is regulated by thermotaxis [30, 31]. The temperature gradient allows sperm to orientate their swim away from the utero-tubal junction (low temperature) towards the warmer ampulla where the oocyte awaits [3234]. Thermotaxis of bull sperm was confirmed involving both calcium channels and intracellular stored calcium [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another physical environment that worked on to facilitate sperm migration to the upper layer of the conical vessel is thermotaxis It has been reported that the migration of sperm in the female reproductive tract associated with fertilization is regulated by thermotaxis [30, 31]. The temperature gradient allows sperm to orientate their swim away from the utero-tubal junction (low temperature) towards the warmer ampulla where the oocyte awaits [3234]. Thermotaxis of bull sperm was confirmed involving both calcium channels and intracellular stored calcium [34].…”
Section: Discussionmentioning
confidence: 99%
“…The temperature gradient allows sperm to orientate their swim away from the utero-tubal junction (low temperature) towards the warmer ampulla where the oocyte awaits [3234]. Thermotaxis of bull sperm was confirmed involving both calcium channels and intracellular stored calcium [34]. Our SSRT method utilized this combined mechanisms of migration dynamics sensitive to temperature and rheological stimuli, and the obtained data indicate not only improvement of cryosurvival of prefreeze selected spermatozoa but compelling results in AI provide a solid evidence that pre-selection of high quality spermatozoa prior to cryopreservation by SSRT method is a robust means of improving the fertilization potential of bull semen.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of these selected spermatozoa for ICSI in mice increased cleavage rates and blastocyst production, as well as implantation and live birth rate as opposed to the use of spermatozoa selected by SU. Although this is the only work related to the use of spermatozoa selected by thermotaxis in ARTs, a recent study carried out in bulls has shown that seminal samples delivering high pregnancy rates after artificial insemination show a greater response to thermotaxis (Mondal et al, 2016). However, as in the case of rheotaxis and chemotaxis, there are still no available publications showing the capability of sperm selection by thermotaxis to improve the ARTs efficiency in the human clinic.…”
Section: Sperm Selection Based On Guidance Mechanismsmentioning
confidence: 99%
“…Currently, three guidance mechanisms are known for the sperm movement including thermotaxis (swimming due to temperature gradient), Rheotaxis (swimming due to fluid flow gradient), and chemotaxis (swimming due to concentration difference of chemoattractants) which have been demonstrated in human, rabbit, mice, bull and pig [ 3 , 17 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. How chemotaxis occur in sperm through the involvement of ORs and TRs is the focus of this review as expression or suppression of these receptors effect motility, fertility, and viability of post-thaw sperm.…”
Section: Sperm Chemotaxis and Sperm–egg Interactionmentioning
confidence: 99%